Estrategias y Políticas en atención al sobrepeso y obesidad en preescolares y escolares - Rivera-Barragán, María Del Rosario; Ramírez González, Issa María; Acosta Cervantes , Maria del Carmen; Hernández Diaz, Mitzi Nayeli (Horizonte Sanitario, 2021)
Objective: To present some of the strategies and policies that have been implemented regarding the attention to overweight and obesity in pre-school and school children.Materials and methods: The article shows the collection of bibliographic information in the PudMed, SciELO, Infomed, PAHO databases and the Google Scholar search engines, by entering keywords to search for original articles, theses, other bibliographic review articles and journals with a high citation index published from 1994 to 2019, in Spanish or English.Results: A selection was made of 32 articles and publications of the WHO, FAO, Secretary of Health and INSP among others. Of these, the programs and policies that have been established at a national and international level were reviewed for the prevention and attention to the problems related to overweight and obesity, reviewing the actions implemented in each one, as well as the scope and impact that they have had in the population.Conclusion: It is known that the problem of overweight and obesity occupies the first places in mortality and morbidity at a national and international level. In Mexico, if programs and policies that contribute to reducing this health problem in the population are not attended to and implemented, the increase in overweight and obesity will generate comorbidities related to chronic degenerative diseases, or deaths at younger ages and higher costs in terms of health.Keywords: Strategies, policies, overweight and obesity